Generation and characterisation of scalable and stable human pluripotent stem cell-derived microvascular-like endothelial cells for cardiac applications - Qasim A. Majid; Bishwa R. Ghimire; Bela Merkely; Anna M. Randi; Sian E. Harding; Virpi Talman; Gábor Földes (Angiogenesis, 2024)
Coronary microvascular disease (CMD) and its progression towards major adverse coronary events pose a significant health challenge. Accurate in vitro investigation of CMD requires a robust cell model that faithfully represents the cells within the cardiac microvasculature. Human pluripotent stem cell-derived endothelial cells (hPSC-ECs) offer great potential; however, they are traditionally derived via differentiation protocols that are not readily scalable and are not specified towards the microvasculature. Here, we report the development and comprehensive characterisation of a scalable 3D protocol enabling the generation of phenotypically stable cardiac hPSC-microvascular-like ECs (hPSC-CMVECs) and cardiac pericyte-like cells. These were derived by growing vascular organoids within 3D stirred tank bioreactors and subjecting the emerging 3D hPSC-ECs to high-concentration VEGF-A treatment (3DV). Not only did this promote phenotypic stability of the 3DV hPSC-ECs; single cell-RNA sequencing (scRNA-seq) revealed the pronounced expression of cardiac endothelial- and microvascular-associated genes. Further, the generated mural cells attained from the vascular organoid exhibited markers characteristic of cardiac pericytes. Thus, we present a suitable cell model for investigating the cardiac microvasculature as well as the endothelial-dependent and -independent mechanisms of CMD. Moreover, owing to their phenotypic stability, cardiac specificity, and high angiogenic potential, the cells described within would also be well suited for cardiac tissue engineering applications.

Development of a pro-arrhythmic ex vivo intact human and porcine model: cardiac electrophysiological changes associated with cellular uncoupling - Joseph Brook; Min-young Kim; Simos Koutsoftidis; David Pitcher; Danya Agha-Jaffar; Annam Sufi; Catherine Jenkins; Konstantinos Tzortzis; Suofeiya Ma; Richard J. Jabbour; Charles Houston; Balvinder S. Handa; et al. (Pflügers Archiv - European Journal of Physiology, 2020)
We describe a human and large animal Langendorff experimental apparatus for live electrophysiological studies and measure the electrophysiological changes due to gap junction uncoupling in human and porcine hearts. The resultant ex vivo intact human and porcine model can bridge the translational gap between smaller simple laboratory models and clinical research. In particular, electrophysiological models would benefit from the greater myocardial mass of a large heart due to its effects on far-field signal, electrode contact issues and motion artefacts, consequently more closely mimicking the clinical setting. Porcine ( n = 9) and human ( n = 4) donor hearts were perfused on a custom-designed Langendorff apparatus. Epicardial electrograms were collected at 16 sites across the left atrium and left ventricle. A total of 1 mM of carbenoxolone was administered at 5 ml/min to induce cellular uncoupling, and then recordings were repeated at the same sites. Changes in electrogram characteristics were analysed. We demonstrate the viability of a controlled ex vivo model of intact porcine and human hearts for electrophysiology with pharmacological modulation. Carbenoxolone reduces cellular coupling and changes contact electrogram features. The time from stimulus artefact to (-dV/dt) max increased between baseline and carbenoxolone (47.9 ± 4.1–67.2 ± 2.7 ms) indicating conduction slowing. The features with the largest percentage change between baseline and carbenoxolone were fractionation + 185.3%, endpoint amplitude − 106.9%, S-endpoint gradient + 54.9%, S point − 39.4%, RS ratio + 38.6% and (-dV/dt) max − 20.9%. The physiological relevance of this methodological tool is that it provides a model to further investigate pharmacologically induced pro-arrhythmic substrates.

Multi-cellularity in cardiac tissue engineering, how close are we to native heart tissue? - Thomas J. Owen; Sian E. Harding (Journal of Muscle Research and Cell Motility, 2019)

Estrogen deficiency compromised the β2AR-Gs/Gi coupling: implications for arrhythmia and cardiac injury - Hongjian Hou; Zhiwei Zhao; Jeremiah Ong’achwa Machuki; Lin Zhang; Yan Zhang; Lu Fu; Jinxia Wu; Yuyu Liu; Sian E. Harding; Hong Sun (Pflügers Archiv - European Journal of Physiology, 2018)

Contractile effects of adenovirally-mediated increases in SERCA2a activity: A comparison between adult rat and rabbit ventricular myocytes - Babar Chaudhri; Federica del Monte; Roger J. Hajjar; Sian E. Harding (Molecular and Cellular Biochemistry, 2003)